'Actors in the Same Tragedy': Bertrand Russell, Humanism, and The Conquest of Happiness. (November 2015) - Urban, Eva
Abstract : In Writings on Cities Henri Lefebvre calls for a 'renewed right to urban life'. He maintains that 'we must thus make the effort to reach out towards a new humanism, a new praxis, another man, that of urban society'. City spaces are used in a number of contemporary Irish site-specific theatre productions to explore histories of oppression and social injustice, and to imagine a new humanist praxis for society. The international multi-artform production The Conquest of Happiness (2013) was inspired by Bertrand Russell's commitment to human happiness in defiance of war and suffering in his book The Conquest of Happiness (1930) and in his many political and philosophical writings. In this article Eva Urban critically examines the ways in which the performance in Northern Ireland attempted to embody Russell's humanism and related critical concepts to encourage active citizenship. She considers to what extent the dramaturgical options employed inthe production applied Russell's ideas and those of other thinkers by developing critical representations of inhumanity, challenging authoritarianism, and exploring humanist ideals. Eva Urban is a British Academy Postdoctoral Research Fellow in the Faculty of English, University of Cambridge, and an Associate of Clare Hall, Cambridge. She is theauthor of Community Politics and the Peace Process in Contemporary Northern Irish Drama (Peter Lang, 2011) and her articles on political drama and Irish studies have been published in New Theatre Quarterly, Etudes Irlandaises, and Caleidoscopio .